Accelerometer measured sedentary behavior and physical activity in white and black adults: The REGARDS study. Issue 4 (April 2016) - Hooker, Steven P.; Hutto, Brent; Zhu, Wenfei; Blair, Steven N.; Colabianchi, Natalie; Vena, John E.; Rhodes, David; Howard, Virginia J.
Abstract: Objectives: Health disparities between subgroups may be partially due to differences in lifestyle behaviors such as sedentariness and physical activity. To obtain a more accurate description of these two lifestyle behaviors, accelerometry was employed among a large sample of white and black adults (ages 49–99 years) living in the United States. Design: Cross-sectional. Methods: 7967 participants from the REasons for Geographic and Racial Differences in Stroke cohort wore an Actical™ accelerometer ≥10 h/day for ≥4 days. Time (mean minutes/day and proportion of total wear time) spent in sedentary behavior, light intensity physical activity, and moderate-vigorous intensity physical activity was compared by sex, age, body mass index, race, and geographic location. Results: Proportion of total wear time spent in sedentary behavior was 75–90%, light intensity physical activity was 10–23%, and moderate-vigorous intensity physical activity was 0–1.7% across subgroups. Mean moderate-vigorous intensity physical activity was 0–16 min/day and associated with 3–12% accumulating ≥150 min/wk using a 10-min bout criterion. Persons ≥85 years, those classified obese, persons living in the southeastern United States, and black women were the most inactive. The proportion achieving at least one 10-min bout of moderate-vigorous intensity physical activity per week was only 36%. The number of 10-min bouts/week was 1.5 ± 0.08 bouts/week. The distribution of weekly moderate-vigorous intensity physical activity was similar across nearly all subgroups with a distinct reverse J-shaped configuration. Conclusions: The vast majority of white and black midlife and older adults in this study engaged sparingly in moderate-vigorous intensity physical activity, accumulated tremendous amounts of sedentary behavior, and seldom engaged in continuous bouts of health-enhancing physical activity.